Face Bypass Damper Application To Overcome Air Conditioning Oversizing Issue - Abdul Halim, Abdul Qayyum; Tee, Boon Tuan; Wan Mat Zain, Wan Shah Waliallah (Joint Journal of Novel Carbon Resource Sciences & Green Asia Strategy, 2021)
The purpose of this work is to study the impact of a face bypass damper in tackling mould problem caused by an oversized air conditioning system. Comparison was made between the performance of an actual operating AHU and the performance of the AHU after the installation of face bypass damper. Comparison is also made to various simulated model using building energy simulation software to study its effectiveness in solving actual problem. Both actual and simulated result of the face bypass damper shows that it is effective in reducing relative humidity. However, it should not be preferred over a complete replacement with a correctly size AHU due to the energy penalty it incurs.